Steamboat buffet restaurant quality attributes and customer satisfaction / Zuratulraha Jaafar - Jaafar, Zuratulraha (2013)
As the steamboat buffet restaurant industry grows in popularity, it has become increasingly competitive. In such an environment, marketers are understandably concerned about how to maintain or increase market share through better restaurant perceive quality and effective segmentation strategies. This study conducted to identify the important attributes of perceives quality (food quality, service quality and atmospheric quality) in the steamboat buffet restaurant industry from the customer’s perspective. Correlation analysis revealed that there is a relatively strong significant linear relationship between perception perspective of customer and the elasticity for a restaurant’s attributes is positive and direct, and the current results as well support this assumption. Results also indicated that food quality attributes stands tall as the main dimension that customer perceived in visiting steamboat buffet restaurant, followed by the second attributes which is atmospheric quality. This study should have a significant impact on the restaurant industry, especially steamboat buffet sector as it identifies the scope of differential returns on investment on various restaurant attributes and its attributes.